The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1002/ijc.10716
|View full text |Cite
|
Sign up to set email alerts
|

Association of chili pepper consumption, low socioeconomic status and longstanding gallstones with gallbladder cancer in a Chilean population

Abstract: We explored the risk factors for gallbladder cancer and explanations for its sharp and constant incidence increase in Chile since the 1970s. We compared 114 consecutive patients with verified gallbladder cancer, diagnosed 1992-1995, to 114 matched hospital patients with gallstones, using conditional logistic regression analysis. Low education showed a nonsignificant positive relationship with gallbladder cancer [odds ratio (OR) ‫؍‬ 2.3, 95% confidence interval (CI) 0.8 -6.2], and low socioeconomic level showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
100
0
6

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 131 publications
(109 citation statements)
references
References 28 publications
3
100
0
6
Order By: Relevance
“…The eight cohort studies Wolk et al, 2001;Calle et al, 2003;Samanic et al, 2004Samanic et al, , 2006Engeland et al, 2005;Kuriyama et al, 2005;Oh et al, 2005) and three case -control studies Zatonski et al, 1997;Serra et al, 2002) that were included in the meta-analysis involved a total of 3288 cases. Main characteristics of the studies are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The eight cohort studies Wolk et al, 2001;Calle et al, 2003;Samanic et al, 2004Samanic et al, , 2006Engeland et al, 2005;Kuriyama et al, 2005;Oh et al, 2005) and three case -control studies Zatonski et al, 1997;Serra et al, 2002) that were included in the meta-analysis involved a total of 3288 cases. Main characteristics of the studies are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Main characteristics of the studies are shown in Table 1. Weight and height were measured in three studies (Engeland et al, 2005;Oh et al, 2005;Samanic et al, 2006) and self-reported in five studies Zatonski et al, 1997;Serra et al, 2002;Calle et al, 2003;Kuriyama et al, 2005); in three studies, obesity was defined by a discharge diagnosis of obesity Wolk et al, 2001;Samanic et al, 2004). Among case -control studies, one used population-based controls (Zatonski et al, 1997) and two used hospital-based controls Serra et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations